Pride and prejudice in teaching History in Brazil: Reflections about the curricula, teacher training and textbooks - José da Silva, Giovani; Meireles, Marinelma Costa (Revista Crítica Histórica, 2017)
In a historical moment in which we’ve been discussing about an elaboration of a National Curricular Common Base for the Basic Brazilian Education, reflections about teachers training, curricula and textbooks are necessary. With a few variations, the Teaching History in Brazil is still ruled by the Eurocentrism, through the idea of the History of a country is a derivation of the European expansion and by the denial of the protagonism of indigenous populations, Africans and their descendants, as well as other peoples. The recent clashes between professional historians, History teachers, and education specialists in the school curriculum component show that there are different conceptions in dispute about what students in Brazil should learn about History. The purpose of the text is to problematize such situation, questioning and presenting alternatives to combat racism in History Teaching in Brazil so that the young Brazilians who finish their studies in Basic Education be proud of their origins. Curricula that present a linear history, in stages and with evolutionary characteristics, as well as teacher training courses and didactic materials that crystallize and consecrate only a European version of History make it impossible to change the status quo.